High-thermal-conductivity composite film and preparation method thereof
By adopting the combination of high heat -conducting composite membrane and using the coating type or stretching method polytamide film and thermal conductivity, the problem of traditional heat dissipation film materials is too large and the insulation effect is not satisfactory, and more efficient heat dissipation The effect of the insulation, while reducing the cost.
Patent Information
- Application Number
- CN202411661610.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-28
AI Technical Summary
Traditional heat dissipation adhesive film materials need to consider insulation characteristics, resulting in too large product thickness, unsatisfactory heat dissipation and insulation effects, and adding too much heat dissipation powder makes the surface of the material fragile and difficult to use.
The high heat -conducting composite film includes at least two layers of high molecular film and at least one layer of thermal conductivity and sticky layer with heat dissipation powder. The thermal adhesive layer is located between the two adjacent high -molecular film. The polymer thin film is a coating type or stretching method polytamide film. The thickness of the heating and sticky layer is 5-100um, and the thickness of the composite film is 15-800 μm.
The overall thickness of the product is thinner, the heat dissipation efficiency is high, and at the same time ensure the insulation effect, reducing the overall cost.
Smart Images

Figure CN119371903A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heat dissipation adhesive films, and in particular relates to a high thermal conductivity composite film and a preparation method thereof. Background Art
[0002] Traditional heat dissipation film materials need to consider insulation properties. In order to achieve a thermal conductivity of 3w / (m*k) and a breakdown voltage of 7~10KV, the thickness of the adhesive used to bond the copper foil layer needs to be 120 to 150um or even higher to meet the insulation requirements. Therefore, the total thickness of the product will be very large. Insufficient thickness will result in unsatisfactory heat dissipation and insulation effects. It is also easy to make the surface of the material too fragile and difficult to use for subsequent processing due to the addition of too much heat dissipation powder. For the heat dissipation effect, the use of modified stretched polyimide film can effectively reduce the overall thickness to meet its insulation properties and operability. However, its thermal conductivity is mostly between 0.4~0.8w / (m*k). The overall unit thermal resistance of the product is still high, which leads to high costs. A sufficiently good thermal conductive film is required to ensure both heat dissipation performance and insulation.
[0003] Therefore, how to develop products with good voltage breakdown resistance and heat dissipation performance, reduce overall costs, and produce thermally conductive polymer films through simplified processes are issues that need to be urgently addressed. Summary of the invention
[0004] The main technical problem solved by the present invention is to provide a high thermal conductivity composite film and a preparation method thereof. The coated polyimide film or stretched polyimide film of the high thermal conductivity composite film can make the composite film have excellent insulation properties, making the overall thickness of the product thinner and the heat dissipation efficiency high, and is matched with a thermally conductive adhesive layer to supplement the overall heat dissipation and insulation effects.
[0005] In order to solve the above technical problems, a technical solution adopted by the present invention is: a high thermal conductivity composite film, comprising at least two layers of polymer films and at least one layer of thermal conductive adhesive layer having heat dissipation powder, wherein the thermal conductive adhesive layer is located between two adjacent layers of the polymer films;
[0006] The polymer film is a coated polyimide film or a stretched polyimide film;
[0007] The thickness of the thermally conductive adhesive layer is 5 to 100 um;
[0008] The thickness of the high thermal conductivity composite film is 15 to 800 μm;
[0009] The content of the thermally conductive powder in the thermally conductive adhesive layer is 50-85wt%, and the particle size of the thermally conductive powder is 0.5-10μm. The coated polyimide film or the stretched polyimide film of the high thermal conductivity composite film of the present invention can make the composite film have excellent insulation performance, making the overall thickness of the product thinner and the heat dissipation efficiency high, and the thermally conductive adhesive layer is used to supplement the overall heat dissipation effect and insulation effect.
[0010] Furthermore, the thermally conductive adhesive layer is selected from at least one of epoxy resin, acrylic resin, urethane resin, silicone rubber resin, polyparacycloxylene resin, bismaleimide resin and polyimide resin;
[0011] The thermally conductive powder is selected from at least one of zirconium oxide, calcium carbonate, silicon carbide, boron nitride, aluminum oxide, talc, aluminum nitride, glass powder, graphite and graphene.
[0012] Furthermore, the coated polyimide film includes a polyimide varnish layer, and the polyimide varnish layer is composed of the following components:
[0013] (1) Polyimide resin, 50 to 95% by weight;
[0014] (2) Epoxy resin, 0 to 25% by weight;
[0015] (3) Inorganic filler, 0 to 20% by weight;
[0016] (4) Catalyst, weight percentage 0 to 10%.
[0017] Further, the polyimide resin is at least one of a polyimide resin and a polyamideimide, and its components include a diamine, an acid anhydride, an isocyanate, a tertiary amine and a solvent, and its components are synthesized into at least one of a polyimide resin or a polyamideimide;
[0018] The epoxy resin is at least one of glycidylamine epoxy resin, glycidyl ester epoxy resin, epoxidized olefin compound, alicyclic epoxy resin, polyphenol glycidyl ether epoxy resin, bisphenol A epoxy resin, bisphenol F epoxy resin, aliphatic glycidyl ether epoxy resin, heterocyclic and mixed epoxy resins. The epoxy resin can be used as a crosslinking agent to effectively improve the overall reactivity;
[0019] The catalyst is at least one of 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole and 1-benzyl-2-phenylimidazole;
[0020] The inorganic filler is at least one of calcium sulfate, carbon black, silicon dioxide, titanium dioxide, zinc sulfide, zirconium oxide, calcium carbonate, silicon carbide, boron nitride, aluminum oxide, aluminum hydroxide, talc, aluminum nitride, glass powder, quartz powder and clay, or contains at least one flame retardant compound of halogen, phosphorus, nitrogen or boron, and the particle size of the inorganic filler is 0.5-10 μm;
[0021] The flame retardancy of the powder increases with different proportions. When higher flame retardancy is required, one or more mixtures of inorganic substances such as aluminum hydroxide, aluminum oxide, calcium carbonate and one or more flame retardant compounds of halogen, phosphorus, nitrogen or boron are preferred; when higher thermal conductivity is required, inorganic substances such as aluminum oxide, nitrogen or boron are preferred.
[0022] Further, the diamine is selected from at least one of 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-diaminodiphenyl ether, bis[4-(3-aminophenoxy)phenyl]sulfonamide, bis[4-(4-aminophenoxy)phenyl]sulfonamide, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, bis[4-(4-aminophenoxy)phenyl]methane, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]ethyl ether, bis[4-(4-aminophenoxy)phenyl]ketone, 1,3-bis(4-aminophenoxy)benzene, and 1,4-bis(4-aminophenoxy)benzene;
[0023] The acid anhydride is selected from at least one of hexafluorodianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, 1,2-ethylenebis[1,3-dihydro-1,3-dioxoisobenzofuran-5-carboxylate], 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, trimellitic anhydride, and cis-aconitic anhydride;
[0024] In the synthesis of polyamide-imide, the molar ratio of all diamines / all acid anhydrides is 1 / 2.05 to 2.20. In the synthesis of polyimide resins, the molar ratio of all diamines / all dianhydrides is 1 / 0.90 to 1.10;
[0025] The isocyanate is selected from at least one of 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, naphthalene-1,5-diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and lysine diisocyanate. In the synthesis of the polyamide-imide, the molar ratio of all diamines / isocyanates is 1 / 1.00 to 1.50;
[0026] The tertiary amine is selected from at least one of triethylamine, isoquinoline, pyridine, N-ethylpiperidine, and benzimidazole, and its addition amount as a catalyst is 0 to 3% by weight;
[0027] The solvent is selected from at least one of N-methylpyrrolidone, γ-butyrolactone, cyclohexanone, acetone, butanone, N,N-dimethylformamide, N,N-dimethylacetamide, pyridine, cyclohexane, dichloromethane, tetrahydrofuran, ethyl acetate, acetonitrile, 1,2-dichloroethane, trichloroethylene, triethylamine, 4-methyl-2-pentanone, toluene, and xylene.
[0028] Furthermore, the coated polyimide film has a carrier film on its surface, and the carrier film is at least one of polypropylene, biaxially oriented polypropylene, polyethylene terephthalate, polyimide, polyphenylene sulfide, polyethylene naphthalate, polyurethane, and polyamide;
[0029] The thickness of the carrier film is 12.5 to 250 μm, the thickness of the polyimide varnish layer is 1 to 150 μm, the polyimide varnish layer can be a single layer generated by one-time curing or multiple layers generated by multiple coating and curing. By means of multi-layer coating and curing of the varnish-type resin insulating layer, the micropores existing in the coating process can be solved, the micropore problem on the surface can be solved, and it is beneficial to improve the mechanical properties, insulation, and processing operability.
[0030] Furthermore, the thickness of the stretched polyimide film is 5 to 50 μm;
[0031] The thickness of the coating type polyimide film is 2 to 25 um, preferably 5 to 12 um.
[0032] Furthermore, the present invention also provides a method for preparing a coated polyimide film, comprising the following two methods:
[0033] Method 1: It includes the following steps:
[0034] Step 1: coating a polyimide varnish layer on a carrier film, and curing the polyimide varnish layer at a low temperature of 50 to 180° C.;
[0035] Step 2: If multiple curing steps are still required, the polyimide varnish layer can be formed according to the coating parameters and curing temperature of step 1.
[0036] Method 2: includes the following steps:
[0037] Step 1: coating a polyimide varnish layer on a carrier film, and drying in an oven to form a polyimide varnish layer;
[0038] Step 2: Continue to apply other polyimide varnish layers on the dried polyimide varnish layer;
[0039] Step 3: After all the polyimide varnish layers are coated, a low temperature curing at 50 to 180° C. is finally performed to form the polyimide varnish layer.
[0040] The present invention also provides a method for preparing a high thermal conductivity composite film, wherein the polymer film uses a coated polyimide film in the preparation process, and the method comprises the following steps:
[0041] Step 1: Coat a thermally conductive adhesive layer on a polymer film, dry it in an oven to remove the solvent, and then press another polymer film to obtain a high thermally conductive composite film still with a carrier film;
[0042] Step 2: If continuous lamination is required to increase the thickness, the product obtained in step 1 is coated with a thermally conductive adhesive layer after the carrier film is removed from one side on a continuous production line, and then pressed with another polymer film after drying in an oven to remove the solvent, thereby obtaining a thickened high thermal conductive composite film with a carrier film;
[0043] Step 3: Put the finished product obtained in step 2 on a machine to tear off the carrier film and roll up the final high thermal conductivity composite film.
[0044] The present invention also provides a method for preparing a high thermal conductivity composite film, wherein the polymer film uses a stretched polyimide film, and the method comprises the following steps:
[0045] Step 1: coating a thermally conductive adhesive layer on a polymer film, drying it in an oven to remove the solvent, and then laminating it with another polymer film to obtain the high thermal conductive composite film of the present invention;
[0046] Step 2: If continuous lamination is required to increase the thickness, the product obtained in step 1 is coated with a thermally conductive adhesive layer, dried in an oven to remove the solvent, and then pressed with another polymer film, and rolled up to obtain a thickened high thermal conductive composite film.
[0047] The beneficial effects of the present invention include at least the following points:
[0048] The coated polyimide film or the stretched polyimide film of the high thermal conductivity composite film of the present invention can make the composite film have excellent insulation performance, making the overall thickness of the product thinner and the heat dissipation efficiency high, and is matched with a thermally conductive adhesive layer to supplement the overall heat dissipation effect and insulation effect;
[0049] The high thermal conductivity composite film of the present invention is prepared by a simple process and the overall cost is lower than that of a single thermal conductive adhesive film or a modified thermal conductive polyimide film. The polymer film is coated with a thermal conductive adhesive layer to make the composite film. All sections are rolled up in large quantities and do not need to be aged. The thermal conductive composite film is directly coated. This process improves the yield, reduces loss, improves efficiency, and saves costs. When higher insulation or reinforcement effects are required, the composite film of the present application can also be multiplied by a composite method of a polymer film and a thermal conductive adhesive layer to achieve a total thickness that is difficult to achieve with a single composition.
[0050] The polyimide film with carrier film and the high thermal conductivity composite film using the film of the present invention are lower in cost than the thermal conductive adhesive film of a single medium or the thermal conductive polymer film (such as polyimide modification) under the same thermal resistance and insulation. In addition, when the coated polyimide film is produced continuously for a long time, the carrier has good operability during coating, which can greatly improve the yield and efficiency, thereby simplifying the process technology, reducing costs, and improving product competitiveness.
[0051] The polyimide varnish of the present invention can be designed in multiple layers and combined with methods such as changing the resin ratio or doping powders, and by improving the powder content ratio and designing the particle size, an insulating layer with multiple advantages such as high insulation, high flame retardancy, high thermal conductivity, and high mechanical properties can be obtained. In addition, the varnish-type insulating layer has better dimensional stability than the film produced by the cast film process because there is no residual stress from stretching during the process. In the thin film scenario, the varnish-type insulating layer is directly generated on the carrier film, which is easier to process in the downstream process. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 It is a schematic diagram of the stacking structure of a coated polyimide film of the present invention;
[0053] Figure 2 It is a schematic diagram of the stacking structure of a high thermal conductivity reinforcing plate using a coated polyimide film or a stretched film of the present invention;
[0054] Figure 3 It is a schematic diagram of a stacked structure of a high thermal conductive composite film using a coated polyimide film or a stretched film according to the present invention;
[0055] Figure 4 This is a schematic diagram of a layer-increasing scheme for the high thermal conductivity composite film of the present invention;
[0056] Figure 5 The present invention combines Figure 3 and Figure 4 Schematic diagram of the stacking structure of the formed high thermal conductivity composite film;
[0057] The parts in the accompanying drawings are marked as follows:
[0058] 100, polymer film; 101, polyimide varnish layer; 102, carrier film; 200, thermal conductive adhesive layer; 300, outer thermal conductive adhesive layer. DETAILED DESCRIPTION
[0059] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0060] Embodiment: A high thermal conductivity composite film and a method for preparing the same, such as Figure 3 He Ru Figure 5 As shown, it includes at least two layers of polymer films 100 and at least one layer of thermally conductive adhesive layer 200 having heat dissipation powder, and the thermally conductive adhesive layer is located between two adjacent layers of the polymer films 100;
[0061] The polymer film 100 is a coated polyimide film or a stretched polyimide film;
[0062] The thickness of the thermally conductive adhesive layer 200 is 5 to 100 um;
[0063] The thickness of the high thermal conductivity composite film is 15 to 800 μm;
[0064] The content of the thermally conductive powder in the thermally conductive adhesive layer 200 is 50-85 wt %, and the particle size of the thermally conductive powder is 0.5-10 μm.
[0065] The thermally conductive adhesive layer 200 is selected from at least one of epoxy resin, acrylic resin, urethane resin, silicone rubber resin, polyparacycloxylene resin, bismaleimide resin and polyimide resin;
[0066] The thermally conductive powder is selected from at least one of zirconium oxide, calcium carbonate, silicon carbide, boron nitride, aluminum oxide, talc, aluminum nitride, glass powder, graphite and graphene.
[0067] The coated polyimide film includes a polyimide varnish layer 101, and the polyimide varnish layer is composed of the following components:
[0068] (1) Polyimide resin, 50 to 95% by weight;
[0069] (2) Epoxy resin, 0 to 25% by weight;
[0070] (3) Inorganic filler, 0 to 20% by weight;
[0071] (4) Catalyst, weight percentage 0 to 10%.
[0072] The polyimide resin is at least one of a polyimide resin and a polyamide-imide, and its components include diamine, anhydride, isocyanate, tertiary amine and solvent, and its components are synthesized into at least one of a polyimide resin and a polyamide-imide;
[0073] The epoxy resin is at least one of glycidylamine epoxy resin, glycidyl ester epoxy resin, epoxidized olefin compound, alicyclic epoxy resin, polyphenol glycidyl ether epoxy resin, bisphenol A epoxy resin, bisphenol F epoxy resin, aliphatic glycidyl ether epoxy resin, heterocyclic and mixed epoxy resins. The epoxy resin can be used as a crosslinking agent to effectively improve the overall reactivity;
[0074] The catalyst is at least one of 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole and 1-benzyl-2-phenylimidazole;
[0075] The inorganic filler is at least one of calcium sulfate, carbon black, silicon dioxide, titanium dioxide, zinc sulfide, zirconium oxide, calcium carbonate, silicon carbide, boron nitride, aluminum oxide, aluminum hydroxide, talc, aluminum nitride, glass powder, quartz powder and clay, or contains at least one flame retardant compound of halogen, phosphorus, nitrogen or boron. The particle size of the inorganic filler is 0.5-10 μm. The increase of powder in different proportions has different flame retardant properties. When higher flame retardancy is required, one or more mixtures of inorganic substances such as aluminum hydroxide, aluminum oxide, calcium carbonate and one or more flame retardant compounds of halogen, phosphorus, nitrogen or boron are preferred; when higher thermal conductivity is required, inorganic substances such as aluminum oxide, nitrogen or boron are preferred.
[0076] The diamine is selected from at least one of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB), 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-diaminodiphenyl ether, bis[4-(3-aminophenoxy)phenyl]sulfonamide, bis[4-(4-aminophenoxy)phenyl]sulfonamide, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, bis[4-(4-aminophenoxy)phenyl]methane, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]ethyl ether, bis[4-(4-aminophenoxy)phenyl]ketone, 1,3-bis(4-aminophenoxy)benzene, and 1,4-bis(4-aminophenoxy)benzene;
[0077] The acid anhydride is selected from at least one of hexafluorodianhydride (6FDA), bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride (B1317), 1,2-ethylenebis[1,3-dihydro-1,3-dioxoisobenzofuran-5-carboxylate], 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, trimellitic anhydride (TMA), and cis-aconitic anhydride;
[0078] In the synthesis of polyamide-imide, the molar ratio of all diamines / all acid anhydrides is 1 / 2.05 to 2.20. In the synthesis of polyimide resins, the molar ratio of all diamines / all dianhydrides is 1 / 0.90 to 1.10;
[0079] The isocyanate is selected from at least one of 4,4'-diphenylmethane diisocyanate (MDI), 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, naphthalene-1,5-diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and lysine diisocyanate. In the synthesis of the polyamide-imide, the molar ratio of all diamines / isocyanates is 1 / 1.00 to 1.50;
[0080] The tertiary amine is selected from at least one of triethylamine (Et3N), isoquinoline, pyridine, N-ethylpiperidine, and benzimidazole, and its addition amount as a catalyst is 0 to 3% by weight;
[0081] The solvent is selected from at least one of N-methylpyrrolidone, γ-butyrolactone, cyclohexanone, acetone, butanone, N,N-dimethylformamide, N,N-dimethylacetamide, pyridine, cyclohexane, dichloromethane, tetrahydrofuran, ethyl acetate, acetonitrile, 1,2-dichloroethane, trichloroethylene, triethylamine, 4-methyl-2-pentanone, toluene, and xylene.
[0082] like Figure 1 As shown, the surface of the coated polyimide film has a carrier film 102, and the carrier film 102 is at least one of polypropylene, biaxially oriented polypropylene, polyethylene terephthalate, polyimide, polyphenylene sulfide, polyethylene naphthalate, polyurethane, and polyamide;
[0083] The thickness of the carrier film 102 is 12.5 to 250 μm, and the thickness of the polyimide varnish layer is 1 to 150 μm. The polyimide varnish layer can be a single layer generated by one-time curing or multiple layers generated by multiple coating and curing. By means of multi-layer coating and curing of the varnish-type resin insulating layer, the micropores existing in the coating process can be solved, the micropore problem on the surface can be solved, and it is beneficial to improve the mechanical properties, insulation, and processing operability.
[0084] The thickness of the stretched polyimide film is 5 to 50 μm;
[0085] The thickness of the coating type polyimide film is 2 to 25 um, preferably 5 to 12 um.
[0086] like Figure 4 As shown, the present invention also provides a method for preparing a coated polyimide film, comprising the following two methods:
[0087] Method 1: It includes the following steps:
[0088] Step 1: coating a polyimide varnish layer on a carrier film, and curing the polyimide varnish layer at a low temperature of 50 to 180° C.;
[0089] Step 2: If multiple curing steps are still required, the polyimide varnish layer can be formed according to the coating parameters and curing temperature of step 1.
[0090] Method 2: includes the following steps:
[0091] Step 1: coating a polyimide varnish layer on a carrier film, and drying in an oven to form a polyimide varnish layer;
[0092] Step 2: Continue to apply other polyimide varnish layers on the dried polyimide varnish layer;
[0093] Step 3: After all the polyimide varnish layers are coated, a low temperature curing at 50 to 180° C. is finally performed to form the polyimide varnish layer.
[0094] The present invention also provides a method for preparing a high thermal conductivity composite film, wherein the polymer film uses a coated polyimide film in the preparation process, and the method comprises the following steps:
[0095] Step 1: Coat a thermally conductive adhesive layer on a polymer film, dry it in an oven to remove the solvent, and then press another polymer film to obtain a high thermally conductive composite film still with a carrier film;
[0096] Step 2: If continuous lamination is required to increase the thickness, the product obtained in step 1 is coated with a thermally conductive adhesive layer after the carrier film is removed from one side on a continuous production line, and then pressed with another polymer film after drying in an oven to remove the solvent, thereby obtaining a thickened high thermal conductive composite film with a carrier film;
[0097] (Continue to repeat step 2 to thicken the product, which is considered as step 2, 3, n...)
[0098] Step 3: Put the finished product obtained in step 2 on a machine to tear off the carrier film and roll up the final high thermal conductivity composite film.
[0099] The present invention also provides a method for preparing a high thermal conductivity composite film, wherein the polymer film uses a stretched polyimide film, and the method comprises the following steps:
[0100] Step 1: coating a thermally conductive adhesive layer on a polymer film, drying it in an oven to remove the solvent, and then laminating it with another polymer film to obtain the high thermal conductive composite film of the present invention;
[0101] Step 2: If continuous lamination is required to increase the thickness, the product obtained in step 1 is coated with a thermally conductive adhesive layer, dried in an oven to remove the solvent, and then pressed with another polymer film, and rolled up to obtain a thickened high thermal conductive composite film.
[0102] (Continue to repeat step 2 to thicken the product, which is considered as step 2, 3, n...)
[0103] In specific implementation, coating temperature: 50 ~ 180 ℃ (a temperature range), pressing temperature and pressure: 90 ~ 150 ℃ (a fixed temperature) & 1 ~ 3kgf / cm 2 .
[0104] When the total thickness does not exceed 500μm, each layer can be continuously produced in large-meter rolls and rolled for packaging; when the total thickness exceeds 500μm, two or more different thermally conductive composite films not exceeding 500μm can be pressed together by roll-to-roll, sheet-to-sheet or roll-to-sheet method and cut into sheets for packaging.
[0105] like Figure 2 As shown, (the thermally conductive reinforcement plate includes: a polymer film, an interlayer thermally conductive adhesive layer, a polymer film, and an outer thermally conductive adhesive layer 300), an outer thermally conductive adhesive layer is provided on the outside of the high thermally conductive composite film of the present invention, which is conducive to composite with other interfaces such as copper foil, aluminum foil, copper plate with aluminum plate or steel strip, steel sheet, FR4, polyimide, etc. The adhesive layer can also be a thermally conductive adhesive layer.
[0106] Polyamide-imide synthesis steps:
[0107] 1. Add 4.11 g of BAPP to 33 g of NMP, introduce nitrogen, and stir at 80°C to dissolve.
[0108] 2. Add 4.03 g TMA and react at 80°C for 1 hour.
[0109] 3. After adding toluene, raise the temperature to 170°C to evaporate the water, and finally raise the temperature to 190°C to evaporate the toluene.
[0110] 4. After cooling back to room temperature, add 3.00g MDI and 0.13g Et3N, raise the temperature to 120℃ and react for 3 hours to complete the soluble polyamide-imide solution.
[0111] * If BAPP is not added in step 1 during the synthesis, MDI can be directly mixed with TMA (MDI:TMA molar ratio = 1.0-1.5:1) and 0-3wt% Et3N to react to complete the soluble polyamide-imide solution.
[0112] For example, 2.10 g of TMA is added with 3.00 g of MDI and 0.10 g of Et3N at room temperature, and the temperature is raised to 120° C. for reaction for 3 hours to complete a soluble polyamide-imide solution.
[0113] Polyimide synthesis steps:
[0114] 1. Under nitrogen, add monomers to 349 g NMP at 80°C, first add 32.02 g TFMB, then add 21.99 g 6FDA and 12.41 g B1317.
[0115] 2. Add 6FDA and B1317 in equal proportions, with the additional amount being 5% of the added amount.
[0116] 3. Raise the temperature to 150°C and add 0.80 g of N-ethylpiperidine.
[0117] 4. Raise the temperature to 190°C and react for 4 hours to obtain a soluble polyimide solution.
[0118] Table 1. Polyimide varnish ratio: (The composition of polyimide and polyamide-imide, refer to the above synthesis steps for equivalent amplification or fine-tuning)
[0119]
[0120] The epoxy resin used is dicyclopentadiene phenolic epoxy resin (DCPD), the catalyst is 2-ethyl-4-methylimidazole, and the inorganic filler in Examples 1 to 4 is SiO 2 (D50 = 0.93 μm), the inorganic filler in Examples 5 and 6 is Al 2 O 3 (D50=1.36μm).
[0121] The varnish obtained from the ratio in Table 1 was matched with a PET carrier (Dupont Teijin Films, YG0), and a polyimide varnish layer was coated on the carrier film and cured at a low temperature of 50 to 180°C to obtain Figure 1 The laminated coated polyimide film is made into corresponding embodiment and comparative example characteristic data, Appendix 2. Coated polyimide film characteristics.
[0122] Table 2. Coating type polyimide film properties
[0123]
[0124] From the results in Table 2, it can be seen that the coating film of the present invention has a reasonable ratio, and the results show that the film has excellent thermal conductivity and insulation properties and is easy to release. The mechanical properties, electrical properties, thermal properties, dimensional stability, etc. are all tested after removing the carrier.
[0125] The ratios in Examples 1 and 6 in Table 1 were selected and matched with a PET carrier (Dupont Teijin Films, YG0), and a polyimide varnish layer was coated on the carrier film and cured at a low temperature of 50 to 180° C. to obtain Figure 1 The laminated coated polyimide film (the varnish layer can be designed to be one or more than two layers of resin varnish layers. After curing, the carrier can be removed to form a coated polyimide film for other laminated structures) and the carrier is torn off to make corresponding embodiments A1 to A3 (A1 / A2 is made in Example 1 in Table 1, and A3 is made in Example 6 in Table 1), which are compared with commercially available black and yellow polyimide films. Comparative examples B1 to B6 are PIAM GF050, PIAM GF030, DuPont 20EN, DuPont 35KBC, DuPont 150MT+, and DuPont 200MT+. The destruction voltages of the above comparative examples are compared to obtain Table 3.
[0126] Table 3. Insulation properties of coated polyimide films
[0127]
[0128]
[0129] It can be concluded from Table 3 that the dielectric strength of the coated polyimide film can reach the level of commercially available yellow polyimide film, which is much better than commercially available black polyimide film and modified thermally conductive polyimide film. In terms of thermal conductivity, the thermal conductivity coefficient can reach a level equivalent to or better than that of commercially available black polyimide film. In addition, the coated polyimide film can correspond to the existing film thickness specifications and can also be easily prepared in a thinner thickness range to further balance the thermal resistance and insulation design requirements (2 to 5 μm can also be prepared).
[0130] In a Figure 3 (The thermally conductive composite film includes a polymer film and a thermally conductive adhesive layer interposed therebetween) In the specific implementation example of the high thermally conductive composite film, the coated polyimide films of Examples A1 and A3 in Table 3 are used as the 5μm and 12μm insulating layers in the examples to obtain Examples C1 to C4. At the same time, Examples C5 and C6 use the commercially available black polyimide films of Comparative Examples B6 and B4 and the modified thermally conductive polyimide films to make similar Figure 3The laminated composite film and the thermally conductive adhesive films of comparative examples D1 and D2, which are only coated with a thermally conductive adhesive layer, are made into a thermally conductive film property comparison as shown in Table 4. The thermally conductive adhesive component used in the embodiment and the comparative example is 30% acrylic resin (BAP-01) and contains 70% boron nitride (D50 = 2.78μm).
[0131] Table 4. Comparison of thermal conductive film properties
[0132]
[0133]
[0134] In the embodiments of Table 4 of this case, except for C1 and C6, which are slightly insufficient in the breakdown voltage, the structures of C2 to C5 can obtain the technical characteristic indicators that the thermal resistance is slightly higher than that of the comparative examples D1 and D2 and the breakdown voltage reaches 7 to 10KV. In particular, the embodiment C5 can reach a breakdown voltage of 17.44KV, which is difficult to achieve with the current single-layer dielectric, and has excellent insulation. From the comparative examples D1 and D2, it can be found that the thermal conductive adhesive film still has a deficiency in the breakdown voltage and the actual processing is not easy to process due to insufficient strength and too brittle materials. It can be seen from the comparative example D2 that the thermal conductivity coefficient reaches 3w / (m*k) and the breakdown voltage reaches 7 to 10KV when the total thickness reaches 150μm.
[0135] pass Figure 3 and Figure 4 The structure is formed by the number of composite superposition layers Figure 5 , a thermally conductive composite film with better reinforcement effect and stronger insulation can be obtained under similar thermal conductivity. Table 5 shows that by using 2 groups Figure 4 Structure Join Figure 3 The structure is used as an example to prove the improvement of insulation. Based on Examples C1, C2, and C5, the polymer films of Examples A1, A3, and B6 are used to make Examples E1 to E3. The thermal conductive adhesive used in the Examples in Table 5 is 30% acrylic resin (BAP-01) and contains 70% boron nitride (D50 = 2.78 μm).
[0136] Table 5. Comparison of thermal conductive composite film properties
[0137]
[0138] From Examples E1 to E3, it can be seen that the insulation is significantly improved while still having relatively excellent thermal conductivity.
[0139] The test methods for thermal conductivity and thermal resistance refer to ASTM D5470, the test methods for breakdown voltage and dielectric strength refer to ASTM D149, the dimensional stability test refers to IPC-TM-6502.2.4C, the measurement of tensile strength, elastic modulus and elongation follows IPC-TM-6502.4.19, and the release force test follows ASTM D3330.
[0140] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A high thermal conductivity composite film, characterized in that: It comprises at least two layers of polymer films (100) and at least one layer of heat-conducting adhesive layer (200) having heat-dissipating powder, wherein the heat-conducting adhesive layer is located between two adjacent layers of the polymer films; The polymer film is a coated polyimide film or a stretched polyimide film; The thickness of the thermally conductive adhesive layer is 5 to 100 um; The thickness of the high thermal conductivity composite film is 15 to 800 μm; The content of the thermally conductive powder in the thermally conductive adhesive layer is 50-85 wt %, and the particle size of the thermally conductive powder is 0.5-10 μm.
2. The high thermal conductivity composite film according to claim 1, characterized in that: The thermally conductive adhesive layer is selected from at least one of epoxy resin, acrylic resin, urethane resin, silicone rubber resin, polyparacycloxylene resin, bismaleimide resin and polyimide resin; The thermally conductive powder is selected from at least one of zirconium oxide, calcium carbonate, silicon carbide, boron nitride, aluminum oxide, talc, aluminum nitride, glass powder, graphite and graphene.
3. The high thermal conductivity composite film according to claim 1, characterized in that: The coated polyimide film comprises a polyimide varnish layer (101), wherein the polyimide varnish layer is composed of the following components: (1) Polyimide resin, 50 to 95% by weight; (2) Epoxy resin, 0 to 25% by weight; (3) Inorganic filler, 0 to 20% by weight; (4) Catalyst, weight percentage 0 to 10%.
4. The high thermal conductivity composite film according to claim 3, characterized in that: The polyimide resin is at least one of a polyimide resin and a polyamide-imide, and its components include diamine, anhydride, isocyanate, tertiary amine and solvent, and its components are synthesized into at least one of a polyimide resin and a polyamide-imide; The epoxy resin is at least one of glycidylamine epoxy resin, glycidyl ester epoxy resin, epoxidized olefin compound, alicyclic epoxy resin, polyphenol glycidyl ether epoxy resin, bisphenol A epoxy resin, bisphenol F epoxy resin, aliphatic glycidyl ether epoxy resin, heterocyclic epoxy resin and mixed epoxy resin; The catalyst is at least one of 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole and 1-benzyl-2-phenylimidazole; The inorganic filler is at least one of calcium sulfate, carbon black, silicon dioxide, titanium dioxide, zinc sulfide, zirconium oxide, calcium carbonate, silicon carbide, boron nitride, aluminum oxide, aluminum hydroxide, talc, aluminum nitride, glass powder, quartz powder and clay, or contains at least one flame retardant compound of halogen, phosphorus, nitrogen or boron series, and the particle size of the inorganic filler is 0.5 to 10 μm.
5. The high thermal conductivity composite film according to claim 4, characterized in that: The diamine is selected from at least one of 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-diaminodiphenyl ether, bis[4-(3-aminophenoxy)phenyl]sulfonamide, bis[4-(4-aminophenoxy)phenyl]sulfonamide, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, bis[4-(4-aminophenoxy)phenyl]methane, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]ethyl ether, bis[4-(4-aminophenoxy)phenyl]ketone, 1,3-bis(4-aminophenoxy)benzene, and 1,4-bis(4-aminophenoxy)benzene; The acid anhydride is selected from at least one of hexafluorodianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, 1,2-ethylenebis[1,3-dihydro-1,3-dioxoisobenzofuran-5-carboxylate], 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, trimellitic anhydride, and cis-aconitic anhydride; In the synthesis of polyamide-imide, the molar ratio of all diamines / all acid anhydrides is 1 / 2.05 to 2.
20. In the synthesis of polyimide resins, the molar ratio of all diamines / all dianhydrides is 1 / 0.90 to 1.10; The isocyanate is selected from at least one of 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, naphthalene-1,5-diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and lysine diisocyanate. In the synthesis of the polyamide-imide, the molar ratio of all diamines / isocyanates is 1 / 1.00 to 1.50; The tertiary amine is selected from at least one of triethylamine, isoquinoline, pyridine, N-ethylpiperidine, and benzimidazole, and its addition amount as a catalyst is 0 to 3% by weight; The solvent is selected from at least one of N-methylpyrrolidone, γ-butyrolactone, cyclohexanone, acetone, butanone, N,N-dimethylformamide, N,N-dimethylacetamide, pyridine, cyclohexane, dichloromethane, tetrahydrofuran, ethyl acetate, acetonitrile, 1,2-dichloroethane, trichloroethylene, triethylamine, 4-methyl-2-pentanone, toluene, and xylene.
6. The high thermal conductivity composite film according to claim 3, characterized in that: The coated polyimide film has a carrier film (102) on its surface, wherein the carrier film is at least one of polypropylene, biaxially oriented polypropylene, polyethylene terephthalate, polyimide, polyphenylene sulfide, polyethylene naphthalate, polyurethane and polyamide; The thickness of the carrier film is 12.5 to 250 μm, and the thickness of the polyimide varnish layer is 1 to 150 μm.
7. The high thermal conductivity composite film according to claim 1, characterized in that: The thickness of the stretched polyimide film is 5 to 50 μm; The thickness of the coated polyimide film is 2-25 um.
8. A method for preparing a coated polyimide film according to any one of claims 1 to 7, characterized in that: There are two methods: Method 1: It includes the following steps: Step 1: coating a polyimide varnish layer on a carrier film, and curing the polyimide varnish layer at a low temperature of 50 to 180° C.; Step 2: If multiple curing steps are still required, the polyimide varnish layer can be formed according to the coating parameters and curing temperature of step 1. Method 2: includes the following steps: Step 1: coating a polyimide varnish layer on a carrier film, and drying in an oven to form a polyimide varnish layer; Step 2: Continue to apply other polyimide varnish layers on the dried polyimide varnish layer; Step 3: After all the polyimide varnish layers are coated, a low temperature curing at 50 to 180° C. is finally performed to form the polyimide varnish layer.
9. A method for preparing a high thermal conductive composite film according to any one of claims 1 to 8, characterized in that: The polymer film uses a coated polyimide film in the preparation process, including the following steps: Step 1: Coat a thermally conductive adhesive layer on a polymer film, dry it in an oven to remove the solvent, and then press another polymer film to obtain a high thermally conductive composite film still with a carrier film; Step 2: If continuous lamination is required to increase the thickness, the product obtained in step 1 is coated with a thermally conductive adhesive layer after the carrier film is removed from one side on a continuous production line, and then pressed with another polymer film after drying in an oven to remove the solvent, thereby obtaining a thickened high thermal conductive composite film with a carrier film; Step 3: Put the finished product obtained in step 2 on a machine to tear off the carrier film and roll up the final high thermal conductivity composite film.
10. A method for preparing a high thermal conductive composite film according to any one of claims 1 to 8, characterized in that: In the preparation process, the polymer film uses a stretched polyimide film, including the following steps: Step 1: coating a thermally conductive adhesive layer on a polymer film, drying it in an oven to remove the solvent, and then laminating it with another polymer film to obtain the high thermal conductive composite film of the present invention; Step 2: If continuous lamination is required to increase the thickness, the product obtained in step 1 is coated with a thermally conductive adhesive layer, dried in an oven to remove the solvent, and then pressed with another polymer film, and rolled up to obtain a thickened high thermal conductive composite film.